Impact of Digital Tools and Applications on the Research Productivity of Arabic and Islamic Studies Students in Pakistan - Nasurullah Qureshi; Abdul Samee Jessar; Muzaffar Ali; Altaf Ahmed (Ijaz Arabi Journal of Arabic Learning, 2026)
The growing influence of digital technologies has reshaped the nature of academic research, offering new opportunities for improving efficiency, accessibility, and innovation. However, within the field of Arabic and Islamic Studies in Pakistan, the adoption and effective use of digital tools remain underexplored. The limited integration of technology in religious academia often restricts students to traditional, manual research methods, which can impede productivity and quality. This study aims to evaluate the impact of digital tools and applications on the research productivity of Arabic and Islamic Studies students in Pakistan, focusing on awareness, usage patterns, institutional access, and perceived effectiveness. A descriptive quantitative research design was employed, utilizing a structured questionnaire distributed among 252 students from public and private universities. The collected data were analyzed using descriptive statistics to identify usage frequency, tool preference, and perceived outcomes. Results revealed that over 90% of respondents were aware of digital research tools, with Islam360 (88%) and Maktaba Shamela (82%) being the most widely used applications. A majority of students reported improved research quality (74%) and productivity (56%) due to the use of digital tools. Nevertheless, challenges such as inadequate training, limited institutional support, and unequal digital access persist. The study concludes that digital tools have significantly enhanced the efficiency, accuracy, and scholarly depth of Arabic and Islamic research in Pakistan. Strengthening institutional support and digital literacy programs could further advance research productivity and innovation within the discipline.